2013
DOI: 10.1111/tan.12211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Killer cell immunoglobulin‐like receptor (KIR) genotypes and haplotypes in Chinese Han population

Abstract: We performed Killer cell immunoglobulin-like receptor (KIR) genotyping on 1271 individuals of Chinese Han origin including 102 families and 965 unrelated individuals. The families (with one child and both parents) were subjected for haplotype analysis. Forty-one different genotypes were identified. The frequencies of the KIR genotypes found in the family panel were confirmed by those found in the unrelated panel. The family study showed segregation of one A haplotype and at least 15 unique B haplotypes. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…The order was adjusted due to the expansion of the sample cohort. For example, the most common B1 haplotype published in 2013 was still described as KH‐C‐001B, but the haplotype B14, which had previously been found to be not so common, was defined as KH‐C‐005B due to the increase in its haplotype frequency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The order was adjusted due to the expansion of the sample cohort. For example, the most common B1 haplotype published in 2013 was still described as KH‐C‐001B, but the haplotype B14, which had previously been found to be not so common, was defined as KH‐C‐005B due to the increase in its haplotype frequency.…”
Section: Resultsmentioning
confidence: 99%
“…K. Jiang et al reported putative KIR haplotypes from unrelated individuals in 2005 . We then analyzed KIR haplotypes using a segregation study on families of Chinese Han origin …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients (n=210) were assigned into two groups depending on the presence or absence of HLA Chinese population from our previous family study (19). One haplotype with unique Cen-and Telmotifs was excluded since it was only observed in one family and the same profile was not detected in the present study.…”
Section: Impact Of Donor Kir -Recipient Hla Mismatch On Clinical Outcmentioning
confidence: 99%
“…Because 5 Cen KIR gene motifs and 6 Tel KIR gene motifs were identified in Chinese population by our previous family study (19), haplotypes of the Cen-and Tel-parts of the KIR locus in Chinese Han were assigned as defined. The gene content of the identified motifs is shown in Because 2DL3 can only be identified in the centromere of the A haplotype, Cen-A/B was defined as harboring 2DL3 and at least one B-haplotype-defining KIRs (2DL2, 2DL5B, and 2DS2).…”
Section: Kir Haplotype Assignmentmentioning
confidence: 99%